Forebrain control of behaviorally-driven social orienting in zebrafish - Stednitz, Sarah J. (Curr Biol, 2018)
Deficits in social engagement are diagnostic of multiple neurodevelopmental disorders, including autism and schizophrenia [1]. Genetically tractable animal models like zebrafish (Danio rerio) could provide valuable insight into developmental factors underlying these social impairments, but this approach is predicated on the ability to accurately and reliably quantify subtle behavioral changes. Similarly, characterizing local molecular and morphological phenotypes requires knowledge of the neuroanatomical correlates of social behavior. We leveraged behavioral and genetic tools in zebrafish to both refine our understanding of social behavior and identify brain regions important for driving it. We characterized visual social interactions between pairs of adult zebrafish, and discovered that they perform a stereotyped orienting behavior that reflects social attention [2]. Furthermore, in pairs of fish, the orienting behavior of one individual is the primary factor driving the same behavior in the other individual. We used manual and genetic lesions to investigate the forebrain contribution to this behavior and identified a population of neurons in the ventral telencephalon whose ablation suppresses social interactions, while sparing other locomotor and visual behaviors. These neurons are cholinergic and express the gene encoding the transcription factor Lhx8a, which is required for development of cholinergic neurons in the mouse forebrain [3]. The neuronal population identified in zebrafish lies in a region homologous to mammalian forebrain regions implicated in social behavior such as the lateral septum [4]. Our data suggest that an evolutionarily conserved population of neurons controls social orienting in zebrafish.